Serotonin toxicity following suicide with citalopram and lamotrigine: A rare case report and literature review - Gholamali Dorooshi; Shafeajafar Zoofaghari; Rokhsareh Meamar (Wolters Kluwer Medknow Publications, 2020)
Serotonin toxicity is a common but often unrecognized toxicological condition. In most cases, a combination of two or more serotonergic drugs can cause serotonin syndrome. We describe a case of serotonin toxicity in a 17-year-old woman, secondary to suicidal ingestion of 1000 mg lamotrigine and 400 mg citalopram, which has been rarely reported. Our patient had a medical history of depression and was treated with lamotrigine and citalopram. She was brought to the emergency room with nausea, diaphoresis, agitation, shivering, tremor, vertigo, ataxia, mydriasis, nystagmus, hyperreflexia, myoclonus, tachycardia, tachypnea, and mild fever. The symptoms and signs were resolved within 3 days following hydration, sedation, and cyproheptadine. Minor cardiovascular symptoms are probably due to the less toxic dose of citalopram. Lamotrigine, especially in combination with other serotonergic drugs, should be considered a cause of serotonin toxicity.